Effects of residential summer camp on body mass index and body composition in type 1 diabetes. Issue 4 (13th February 2018) - Oden, Jon D; Franklin, Brian; Fernandez, Ernesto; Adhikari, Soumya; White, Perrin C
Abstract : Background: Body mass index (BMI) and fat mass may be higher in children with diabetes compared to healthy peers. It is not certain how diabetic children respond to exercise and diet interventions. Objective: To investigate the effect of summer camp on BMI and body composition in children with type 1 diabetes. Methods: Five hundred eighty‐six children (5‐19 years, 518 with type 1 diabetes, 68 without diabetes) were followed while attending camp. BMI z‐scores (BMIz) and body composition (bioelectrical impedance analysis) were measured at the beginning and end of each 19‐day session. Diet and activity were directly supervised, blood glucose closely monitored. A nested diabetic/non‐diabetic sib pair analysis was also conducted. Changes in BMIz and percent fat mass (%FM) were the primary outcomes. Findings were confirmed by analysis of data from 612 campers (549 with diabetes) the following summer. Results: At entry, campers with diabetes had higher BMIz and %FM. They tended to gain BMIz (0.04 ± 0.01) whereas non‐diabetic campers lost (−0.16 ± 0.11, P < .0001). BMIz increases were positively correlated with precamp hemoglobin A1c values. The differences in initial values and changes in BMIz remained when campers with diabetes were compared to their siblings. All experienced a similar reduction in %FM. Similar results were obtained the following summer. Conclusions: Children with diabetes may, therefore, accrue more lean body tissue with increased exercise and a healthy diet than those without diabetes. This effect is greatest in those with initially poor metabolic control.